Análise econômica da cadeia produtiva vitivinícola na Campanha do estado do Rio Grande do Sul - Bertoldo, Jeorgia Gabriela (2024)
The grape production chain is of great socio-economic importance in Brazil, responsible for a large volume of business for the domestic and foreign markets. Brazilian grapes have become a highlight, due to their quality and market approval, as well as the growing emergence of enterprises linked to the chain, which makes the activity an alternative for diversification within agricultural production units. In the last 20 years, wine production has become more prominent and representative in the Campanha Gaúcha region, where the wine agro-industry has strengthened its presence in the domestic market, assuming the position of second largest wine producing region in 2020, responsible for 31% of national production. The general objective of this research was to carry out a socio-economic analysis of the grape production chain in Campanha Gaúcha. The specific objectives are to map the wine production chain in this region; to describe the process of obtaining the IP Vinhos da Campanha, presenting the perception of the agents; and to characterize a wine tourism model located in the municipality of Santana do Livramento/RS. A case study strategy was used as the methodological procedure. The research covered the wineries that are part of the Vinhos da Campanha Gaúcha Association, and data was collected through semi-structured interviews. It was concluded that the chain depends on other regions and even countries to carry out or complete the production, marketing and distribution processes. The role played by the chain's institutions and organizations in the region studied is of great value, given all the actions taken to strengthen the segment. As a result, the Geographical Indication was obtained in 2020. The agents involved in the adoption of the GI have a positive perception of its benefits and believe in the recognition of the GI, both inside and outside the country. However, promoting and supporting the GI requires synergistic actions involving the production chain and the state through public policies. With regard to wine tourism, it was possible to observe that some companies are developing and investing in initiatives that generate a dynamic and competitive environment. There is a consensus among the players that wine tourism can act as a promoter of local development, since it uses the resources present in the territory to carry out its activities. In general terms, viticulture has grown significantly in the region and is gaining prominence on the international stage. The natural resources are favorable to production. The institutions and organizations structure and give recognition to the quality of the wines, mainly through the Campanha Fine Wine Producers Association. There are weaknesses, especially in terms of dependence on other regions to carry out or complete production, commercial or logistical processes. Unlike other products, wine ends up encouraging the end consumer to visit the places where production takes place, so wine tourism can act as a driver of sustainable development. The conclusion is that public authorities have an important role to play in accelerating the progress and prominence of Campanha Gaúcha wines on the world stage, through public policies to promote the concept of GIs in the domestic and foreign markets, thus making Brazilian products more competitive on a global scale.